Exposure of Cleft Lip and Palate Patients to Toxic Elements Released during Orthodontic Treatment in the Study of Non-Invasive Matrices - Mikulewicz, Marcin (PLoS One, 2015)
THE OBJECTIVE: The aim of the study was evaluation of metal ions (nickel and chromium) released from orthodontic appliances in cleft lip and palate patients and the usefulness of non-invasive matrices (saliva and hair). MATERIALS AND METHODS: The material studied consisted of 100 individuals, including 59 females and 41 males of 5 to 16 years of age, which were divided into 3 groups: experimental–patients with cleft lip and palate (36 individuals, the average treatment time 5.74 years); control group–patients without cleft lip and palate, during orthodontic treatment (32 individuals, the average treatment time 1.78 years) and the control group patients without cleft lip and palate, without any orthodontic appliances (32 individuals). Samples (saliva, hair) were collected and subjects underwent a survey by questionnaire. Multi-elemental analyses of the composition of non-invasive matrices was conducted in an accredited laboratory by inductively coupled plasma spectrometry technique ICP-OES. The results were reported as mean contents of particular elements (Cd, Cr, Cu, Fe, Mn, Mo, Ni, Si) in hair and in saliva. RESULTS: The concentration of Cr, Ni, Fe and Cu ions in saliva of cleft lip and palate patients were several times higher as compared with not treated orthodontically control groups and higher than in the group with orthodontic appliances. Among the assessed matrices, hair of cleft lip and palate patients seem to be not a meaningful biomarker. CONCLUSION: It was found that orthodontic appliances used in long-term treatment of cleft lip and palate patients do not release toxic levels of Cr and Ni ions.